2017
DOI: 10.1007/s41061-016-0100-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Materials Synthesis Using Ultrasound

Abstract: Recent applications of ultrasound to the production of nanostructured materials are reviewed. Sonochemistry permits the production of novel materials or provides a route to known materials without the need for high bulk temperatures, pressures, or long reaction times. Both chemical and physical phenomena associated with high-intensity ultrasound are responsible for the production or modification of nanomaterials. Most notable are the consequences of acoustic cavitation: the formation, growth, and implosive col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 131 publications
0
32
0
Order By: Relevance
“…The formation of IONPs by the sonochemical method is due to acoustic cavitation, which involves three basic sequential steps; formation of bubbles followed by growth and implosive collapse that result in high pressure as well as temperature followed by the high cooling rate [32]. The chemical reactions which are involved in the sonochemical method are reported to be driven by intense ultrasonic waves that are strong enough to produce cavitation are oxidation, reduction, dissolution, decomposition, and hydrolysis [47]. Initially, there is a formation of a minute bubble that gradually grows in size due to the fusion of several small particles and once the size of the bubbles reaches to its maximum i.e., threshold than the bubble could not sustain the pressure difference, and consequently, the bubble implosively collapses and generates a localized hotspot through adiabatic compression or shock wave formation within the gas phase of the collapsing bubble [48].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of IONPs by the sonochemical method is due to acoustic cavitation, which involves three basic sequential steps; formation of bubbles followed by growth and implosive collapse that result in high pressure as well as temperature followed by the high cooling rate [32]. The chemical reactions which are involved in the sonochemical method are reported to be driven by intense ultrasonic waves that are strong enough to produce cavitation are oxidation, reduction, dissolution, decomposition, and hydrolysis [47]. Initially, there is a formation of a minute bubble that gradually grows in size due to the fusion of several small particles and once the size of the bubbles reaches to its maximum i.e., threshold than the bubble could not sustain the pressure difference, and consequently, the bubble implosively collapses and generates a localized hotspot through adiabatic compression or shock wave formation within the gas phase of the collapsing bubble [48].…”
Section: Resultsmentioning
confidence: 99%
“…Another application of sonocrystallization is for the generation of nanocrystals and nanostructures [104][105][106][107][108][109][110]. Qian et al reported ultrasonic irradiation as a new method for generating zinc oxide nanocrystals [111].…”
Section: Applicationmentioning
confidence: 99%
“…Ultrasound and microwave irradiations, ball milling and sonophotodeposition, to name a few strategies, represent innovative technologies to the conventional solid-state, wet chemistry and gas phase synthesis procedures. Many review articles are available in the literature, offering a comprehensive discussion on this subject [57][58][59][60][61]. Here, through a few selected examples, we wish to highlight the advantages of using ultrasound, ball milling, sonophotodeposition and sonoelectrodeposition in the synthesis of solid catalysts (and photocatalysts) for the selective oxidation of alcohols to the corresponding aldehydes or carboxylic acids.…”
Section: Figurementioning
confidence: 99%